(untitled) (Journal of Pathology of Nepal, 2015)
Lymphomas, the malignant neoplasms of the reticuloendothelial and lymphatic system, are classified based on characterisitic morphological pattern, immunophenotypic pattern and sometimes distinctive chromosomal aberrations. Most of the intraosseous lymphomas should be metastatic, and primary intraosseous lymphoma is a rare type of lymphoma, which accounts for only about 5% extranodal lymphoma. It accounts for approximately 3% of all primary bone malignancies. We report a case of 54 years lady presented with pain over right thigh since 3 to 4 months which suddenly increased. The clinico-radiological differential diagnosis was fibrous dysplasia, plasmacytoma or metastasis. The histological findings and immunohistochemistry being positive for CD20 and BCL2 negative are those of Lymphoma- Diffuse large B cell type. Radiotherapy and/or chemotherapy is the preferred modality of management.